2020
DOI: 10.1111/rec.13304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat restoration on peatland bird communities

Abstract: Restoration of damaged ecosystems has become an important tool to slow down biodiversity loss and to maintain ecosystem services. Peatland bird populations have shown a substantial decline during the recent decades in Northern Europe as a consequence of peatland drainage. We studied whether restoration of peatlands drained for forestry affects bird communities. We conducted bird surveys at 11 peatlands in Western Finland, where each of the restored and their pristine counterparts were surveyed before restorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…From the ornithological point of view, advances have been made to restore bogs for a few selected species such as the Golden Plover (Plu-vialis apricaria), whose regional decline has been attributed in part to the loss of nesting habitat (Minayeva et al, 2017). Finland presents a particular case, with over 300 km 2 of forested peatlands restored by blocking drainage ditches following agriculture and forestry (Alsila et al, 2021). To our knowledge, the only quantitative assessment of the effectiveness of peatland restoration for birds in northern Europe comes from Alsila et al (2021), who found no response to restoration by peatland specialist birds, based on annual surveys just before restoration and up to 8 y post restoration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the ornithological point of view, advances have been made to restore bogs for a few selected species such as the Golden Plover (Plu-vialis apricaria), whose regional decline has been attributed in part to the loss of nesting habitat (Minayeva et al, 2017). Finland presents a particular case, with over 300 km 2 of forested peatlands restored by blocking drainage ditches following agriculture and forestry (Alsila et al, 2021). To our knowledge, the only quantitative assessment of the effectiveness of peatland restoration for birds in northern Europe comes from Alsila et al (2021), who found no response to restoration by peatland specialist birds, based on annual surveys just before restoration and up to 8 y post restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Finland presents a particular case, with over 300 km 2 of forested peatlands restored by blocking drainage ditches following agriculture and forestry (Alsila et al, 2021). To our knowledge, the only quantitative assessment of the effectiveness of peatland restoration for birds in northern Europe comes from Alsila et al (2021), who found no response to restoration by peatland specialist birds, based on annual surveys just before restoration and up to 8 y post restoration. One key difference in bird life between European and North American bogs, at least in regions where peat extraction occurs, is the prevalence of songbirds and the paucity of ducks and shorebirds in the latter (Desrochers and van Duinen, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our study sites are part of the peatland restoration monitoring network that was established by Metsähallitus Parks & Wildlife Finland and the University of Jyväskylä in 2007 (Elo et al., 2024 ). The peatland restoration network has been a subject of research for over a decade including studies on the effects of drainage and restoration on, for example, peatland hydrology, vegetation, invertebrates, and bird communities (Alsila et al., 2021 ; Elo et al., 2015 ; Haapalehto et al., 2014 ; Maanavilja et al., 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…One of the critical roles of understanding the effects of restoration on avifauna lies in tailoring management strategies to meet the specific needs of bird species. Avian responses to restoration efforts are species-specific (Gaines et al, 2007;Johnson and Sandercock, 2010;Alsila et al, 2020), and understanding these nuances allows us to implement targeted approaches that maximize positive outcomes. By taking into account diverse ecological requirements and behaviors of different avian species, management activities can be fine-tuned to create a supportive environment for their survival and growth.…”
Section: The Value Of Management Activities In Restored Sitesmentioning
confidence: 99%
“…At the heart of restoration efforts, avifauna stands as a focal point in the quest to reclaim our natural heritage. Over the last few decades, ecologists have increasingly recognized the indispensable role of avian species in restoring ecosystems (Majer, 2009;Alsila et al, 2020). Birds, with their unique abilities to influence critical ecological processes such as pollination, seed dispersal, and decomposition, become the vital threads that interweave the fabric of restored habitats.…”
Section: Introductionmentioning
confidence: 99%